CHARACTERISTICS OF NEUTROPHILIC GRANULOCYTES IN POLYPOUS RHINOSINUSITIS - O. A. Kolenchukova (SPb RAACI, 2014)
We have studied functional parameters of neutrophilic granulocytes in patients with polypous rhinosinusitis by means of luminol- or lucigeninependent chemiluminescence induced by zymosan and Staphylococcus aureus. Luminol-enhanced chemiluminescence registered the entire pool of reactive oxygen species (ROS), reflecting total activity of myeloperoxidase and NADPH oxidase etc., whereas lucigenindependent chemiluminescence detected production of superoxide radical anion (·О2 -), as well as NADPH oxidase activivity. Usage of the in vitro stimulation tests allows both modeling of disease conditions, and to suggest origins of granulocyte stimulation, their mobilization potential and integration of intracellular processes. We found the increased rate of ROS formation, both in spontaneous and induced chemiluminescent reaction in luminol-dependent process. We have studied neutrophilic granulocyte response to different stimuli and found an increased luminol-dependent ROS formation in polypous rhinosinusitis in response to bacterial induction.